Important Criteria for Swedish Construction Companies to Choose Environmentally Friendly Concrete - Alireza Bahrami; Moa Lindqvist; Lisa Lindqvist Berglund; Bengt Eriksson (Salehan Institute of Higher Education, 2023)
Today, ordinary Portland cement-based concrete is one of the most important building materials and is widely used in new building constructions, which is an environmental problem, as cement production accounts for 5%-8% of the world's carbon dioxide emissions. Thus, the need for using a more environmentally friendly concrete (EFC) is growing. However, it is stated that the Swedish construction companies are reluctant to change and adopt new construction methods and materials. This research aims to map the important criteria for the Swedish construction companies in order to choose EFC for using in their projects. The study is carried out based on a literature study and a questionnaire survey. The questionnaire is designed considering the significant criteria of EFC derived from the literature study. The respondents from the Swedish construction companies were asked to rate these various criteria. The collected results are presented with bar graphs. The results show that the highest valued criterion by the respondents for the use of EFC in the projects is its long-term properties while the lowest one is the possibility of introducing a specific ceiling for greenhouse gas emissions of companies. Doi: 10.28991/CEJ-2023-09-01-015 Full Text: PDF